Antimalarial Activity of Ethanol Extract of Sampare Leaves (Glochidion sp var. Biak) Against Plasmodium falciparum In Vitro - khairuddin zainuddin umar; Yuri P.Utami; Muhammad A.Y. Ardi (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Malaria is one of the health problems in the world and in Indonesia. This disease is caused by theprotozoan parasite, the genus Plasmodium. Plasmodium falciparum is the most important parasiticdisease with high morbidity and mortality in the world and tropical countries such as Indonesia inparticular. This study aims to determine the activity of sampare leaf extract in inhibiting the growth ofthe FCR-3 strain of the P. falciparum parasite which causes malaria. Sampare leaves were extracted bymaceration method using 70% ethanol. Extract the results extraction were tested against P. falciparumby in vitro method. 32,67% Yield extract resulted from the extraction process. Phytochemical screeningshows the presence of alkaloid compounds, flavonoids, quinones, saponins, and tannins. The ethanolextract of sampare leaves had IC50 antimalarial activity of 0,125 μg/mL and was categorized very well.Keywords: Antimalarial, Glochidion sp var. Biak, IC50, Plasmodium falciparum.